Almost strong $θ(Λ,p)$-continuity for Functions (European Journal of Pure and Applied Mathematics, 2024)
Our main purpose is to introduce the concept of almost strongly θ(Λ, p)-continuous functions. Moreover, some characterizations of almost strongly θ(Λ, p)-continuous functions are considered.
Keywords: $(Λ,p)$-open set; almost strong $θ(Λ,p)$-continuous function